Phosphorus nutrition and partial N substitution of upland rice (Oryza sativa L.) - Golmel Langangmeilu (Department of Agronomy,College of Agriculture, 2019)
A field experiment on ‘Phosphorus nutrition and partial N substitution of upland rice0(Oryza1sativa L.)’ was conducted1at the Instructional0farm, College1of Agriculture, Vellayani,1Thiruvananthapuram during Kharif,-2018 to0study@the influence of different levels of P, to assess the feasibility of partial substitution of inorganic N with FYM, VC and in situ green manure cowpea and to0work1out1the economics/of1cultivation.0The variety used was Aiswarya (PTB 52)./The experiment1was1laid0out0in^randomized^block^design with 11 treatments and three0replications. The0treatments0were0T1:3301kg-P2O51ha-1 and3120/kg1N0ha-1 (100%3N3as3CF), T2:3451kg1P2O5/ha-10and11201kg/N/ha-1 (100%3N3as3CF), 3T3: 30 kg P2O51ha-1/and/1201kg1N1ha-1/(50% N as CF + 50% N as FYM), T4: 45 3kg /P2O51ha-11and3120/kg1N1ha-1/(50% N as CF + 50% N as FYM), T5: 303kg P2O51ha-1 and/120/kg1N/ha-11(50% N as CF, 25% N as FYM and in situ green manure cowpea), T6: 451kg^P2O5^ha-11and-120^kg1N^ha-1 (50% N as CF, 25% N as FYM and in situ green manure cowpea), T7: 30-kg-P2O5-ha-1 and-120-kg-N-ha-1 (50% N as CF + 50% N as VC), T8: 45 kg-P2O53ha-1 and-120-kg-N-ha-1 (50% N as CF + 50% N as VC ), T9 : 30-kg-P2O5-ha-1 and 120 kg N ha-1 (50% N as CF, 25% N as VC and in situ green manure cowpea), T10 : 45 kg-P2O53ha-1 and3120-kg-N-ha-11( 50% N as CF, 25% N as VC and in situ green manure cowpea) and T11: 30-kg-P2O53ha-1 and 60-kg N3ha-11100% N1as CF3(control). Uniform/dose3of 60 kg3K2O/ha-13was3applied to3all treatments except control where it was 30 kg3K2O3ha-1. The results revealed that the treatment T6 (45 kg3P2O5.ha-11and31201kg N3ha-1 with150 % N as CF, 25 % N as FYM and in situ green manure cowpea) produced the tallest plants at harvest. The treatment T5 (301kg/P2O5/ha-13and/120-kg-N-ha-1 with 50 % N as CF, 25 % N as FYM and in situ green manure cowpea) recorded higher tiller number m-23at 60 DAS and harvest and the highest LAI at 60 DAS. The yield0attributes0viz., productive tillers1m-2, grain weight1per panicle and number-of-filled1grains per panicle was significantly higher with the treatment T5 and T6 registered higher number^of1spikelets per1panicle. The treatment1T51recorded maximum grain1and-straw yields of 3357 and14133 kg ha-1 respectively and/was/on par1with T63and1superior-to other treatments. The maximum HI of 0.45 was recorded by the treatments T53and3T6. The results showed favourable influence of treatments on physiological parameters viz., RLWC at flowering, protein content of grain, total DMP and uptake of NPK at harvest. The treatment T6 recorded the highest RLWC of 76.10 per cent and was on par with T5, T3, T93and T8. The protein content of grain was the highest for treatment T4 (4.9 per cent) and was on par with the rest except T2, T93and T11. The total DMP and uptake of1 N,/P/and/K/were improved by the/treatment T5. .The physical properties of-soil viz., bulk density, porosity and WHC were not significantly influenced by the treatments but available N,1P and K status of/the soil1after/the/experiment1were1significantly\influenced-by\the/ treatments. The treatment T51recorded the highest available N and K while T9 produced the highest available P status in the soil. The important weeds observed were Cynodon-dactylon, Echinocloa-colona among grasses, Cyperus-rotundus among sedges and Phyllanthus-niruri, Alternanthera sessilis and Mimosa-pudica among broad leaved weeds. The weed dry1weight@was1significantly1influenced1by1the1treatments2only0at@45-DAS and1the treatment1T5 =produced the lowest weed dry weight. The pests observed in the experimental field were leaf roller, gundhi bug and stem borer and the pest population did not exceed the economic threshold level. Blast incidence was noticed and control measures were taken. .The net1income1and BC ratio1were1significantly2influenced by the treatments1and T5 produced maximum net income of -₹ 47068 ha-1 and BC ratio of 1.63. The result revealed higher growth characters, yield0attributes1and1yield of upland rice=due2to T5./The treatment T5 recorded maximum net income and BC ratio and was followed by T6. Therefore, the1combined1application of 30 kg P2O5 ha-1 and-1203kg0N3ha-1 applied1as 50% N as CF, 25% N as FYM and in situ green manure cowpea along with 600kg1K2O-ha-1/could be-recommended for/upland rice.